A fluorescence probe study of gemini surfactants in aqueous solution: a comparison between n-2-n and n-6-n series of the alkanediyl-a,w-bis (dimethylalkylammonium bromides) - da Silveira Júnior, Pedro Belchior; Tiera, Vera Aparecida de Oliveira; Tiera, Marcio José (Eclética Química, 2007)
Two series of alkanediyl-a,w-bis (dimethylalkylammonium bromide (n-2-n and n-6-n; n=8, 10,12, and 16) have been synthesized and their micelles properties studied in aqueous solution using pyrene, pyrenecarboxaldehyde (PCA) and 1,8 anilinonaphtalene sulfonic acid sodium salt (ANS) as fluorescent probes. The micelles from these surfactants have been characterized on the basis of the information provided by micelle-solubilized fluorescent probes. The obtained results indicated that the surfactant concentration at which a marked decrease in l max parameter of pyrenecarboxaldehyde (PCA) occurs corresponds to the CMC determined by conductimetric measurements. Changes in the emission spectra of ANS and PCA observed in the submicellar range for both surfactants series (n-2-n and n-6-n) were interpreted as formation of pre-aggregates. It was found that the dimeric surfactants with long spacer (s= 6) form more hydrated aggregates when compared with those formed by the n-2-n and C n TAB surfactants series. This was attributed to a more difficult packing of n-6-n surfactant molecules to form micelles.